Effect of mouthwash containing poly l-Lysine and glycerol monolaurate on oral Helicobacter pylori relating to biofilm eradication, anti-adhesion, and pro-inflammatory cytokine suppression - Mutita Wongsuwanlert; Rawee Teanpaisan; Praphansri Ruangsri; Apichat Kaewdech; Somkiat Sunpaweravong; Nuntiya Pahumunto (Elsevier, 2024)
Background/purpose: Helicobacter pylori has been found to be related to periodontitis, and the oral cavity has been considered a reservoir for H. pylori gastritis infection. Thus, this study evaluated the effect of mouthwash containing poly l-Lysine and glycerol monolaurate on inhibiting H. pylori growth, biofilm formation, cell cytotoxicity, adhesion ability, cagA mRNA expression, and pro-inflammatory cytokines stimulated by H. pylori. Materials and methods: Nineteen H. pylori strains were isolated from the oral cavity. The effectiveness of mouthwash containing poly l-Lysine and glycerol monolaurate was examined for its ability to inhibit H. pylori growth and biofilm formation and was tested for cell viability in oral epithelial cells (H357), gastric adenocarcinoma cells (AGS), and periodontal ligament cells (PDL). Additionally, the mouthwash was tested for reducing cagA mRNA expression, adhesion ability to H357 and AGS cells, and pro-inflammatory cytokines stimulated with H. pylori in AGS and PDL cells. Results: The mouthwash containing poly l-Lysine and glycerol monolaurate could eradicate the biofilm by 14.9-19.9% after incubation at 5 min, and cell viability revealed 77.2, 79.8, and 100.0% for AGS, H357, and PDL cells, respectively. Moreover, the mouthwash containing poly l-Lysine and glycerol monolaurate could down-regulate cagA mRNA expression, reduce adhesion of H. pylori by approximately 9.5-47.8% for H357 cells and 24.5-62.9% for AGS cells, and decrease pro-inflammatory cytokines, especially interleukin-8, stimulated with H. pylori. Conclusion: Mouthwash containing poly l-Lysine and glycerol monolaurate could inhibit H. pylori growth and reduce their virulence expression. The mouthwash also revealed low cytotoxicity to oral and gastric cells.